Factors Influencing Hospitalisation of Infants for Recurrent Gastroenteritis in Western Australia - Wang, K.; Yau, K. K. W.; Lee, A. H. (Methods of Information in Medicine, 2003)
Objective: To determine factors affecting length of hospitalisation of infants for recurrent gastroenteritis using linked data records from the Western Australia heath information system.Methods: A seven-year retrospective cohort study was undertaken on all infants born in Western Australia in 1995 who were admitted for gastroenteritis during their first year of life (n = 519). Linked hospitalisation records were retrieved to derive the outcome measure and other demographic variables for the cohort. Unlike previous studies that focused mainly on a single episode of gastroenteritis, the durations of successive hospitalisations were analysed using a proportional hazards model with correlated frailty to determine the prognostic factors influencing recurrent gastroenteritis.Results: Older children experienced a shorter stay with an increased discharge rate of 1.9% for each month increase in admission age. An additional comorbidity recorded in the hospital discharge summary slowed the adjusted discharge rate by 46.5%. Aboriginal infants were readmitted to hospital more frequently, and had an adjusted hazard ratio of 0.253, implying a much higher risk of prolonged hospitalisation compared to non-Aborigines.Conclusions: The use of linked hospitalisation records has the advantage of providing access to hospital-based population information in the context of medical informatics. The analysis of linked data has enabled the assessment of prognostic factors influencing length of hospitalisations for recurrent gastroenteritis with high statistical power.
Keywords: Australian Aborigines; correlated frailty; data linkage; recurrent gastroenteritis